Global contraction or local growth, bleb shape depends on more than just cell structure. (7th September 2015) - Woolley, Thomas E.; Gaffney, Eamonn A.; Oliver, James M.; Waters, Sarah L.; Baker, Ruth E.; Goriely, Alain
Abstract: When the plasma membrane of a cell locally delaminates from its actin cortex the membrane is pushed outwards due to the cell׳s internal fluid pressure. The resulting spherical protrusion is known as a bleb. A cell׳s ability to function correctly is highly dependent on the production of such protrusions with the correct size and shape. Here, we investigate the nucleation of large blebs from small, local neck regions. A mathematical model of a cell׳s membrane, cortex and interconnecting adhesions demonstrates that these three components are unable to capture experimentally observed bleb shapes without the addition of further assumptions. We have identified that combinations of global cortex contraction and localised membrane growth are the most promising methods for generating prototypical blebs. Currently, neither proposed mechanism has been fully tested experimentally and, thus, we propose experiments that will distinguish between the two methods of bleb production. Abstract : Highlights: Pressure driven protrusions aid motility in muscle stem cells. Cell shape is replicated using a mechanical model of membrane, cortex and adhesions. Observed protrusions, with small neck regions, are difficult to reproduce. Localised membrane growth and cortex contraction stabilise the neck region.